Pengaruh Stres Kerja, Beban Kerja dan Kepuasan Kerja terhadap Turnover Intention Karyawan Pada PT. Cipta Sarana Jaya Abadi - Ferdinand Marco Wijaya; Rusdiana Br Simamora; Latersia Br Gurusinga (Pusat Riset dan Inovasi Nasional, 2025)
High turnover intention rates pose a serious challenge to companies because they can disrupt operational stability, reduce productivity, and increase recruitment and training costs. PT Cipta Sarana Jaya Abadi has faced similar challenges, with an increasing number of employee resignations over the past three years. This study aims to analyze the influence of job stress, workload, and job satisfaction on employee turnover intention. A quantitative survey approach was used, with questionnaires distributed to 80 randomly selected respondents. The data were analyzed using multiple linear regression with SPSS. The results showed that job stress and workload have a positive and significant influence on turnover intention, meaning that the higher the stress and workload levels, the higher the employee's desire to leave the company. Conversely, job satisfaction has a negative and significant influence on turnover intention, meaning that the higher the job satisfaction, the lower the employee's intention to resign. Simultaneously, these three variables significantly influence turnover intention, with a coefficient of determination of 44.6%. This means that job stress, workload, and job satisfaction together explain 44.6% of the variation in turnover intention, while the remainder is influenced by factors outside this study. These findings emphasize the importance of managing stress and workload, as well as increasing job satisfaction, as key strategies for reducing employee turnover intentions. The results of this study are expected to provide a basis for company management in designing more effective human resource management strategies to improve employee retention and well-being.